Simulation Of Short Channel Vertical Mosfet Structures - Ooi , Poh Kok (2010)
Recently, the end of the planar bulk complementary metal oxide semiconductor (CMOS) had become visible. Vertical metal oxide semiconductor field effect transistor (VMOST) structures are one of the promising structures for future CMOS technologies. There are still a lot of research needs to be done on the VMOST structures to mature as that of planar CMOS technologies. It is well known that there are many parameters needed to be considered in designing MOSFET. With the aid of computer-aided design, we can optimize the MOSFET parameters faster and with lower cost.